Introduction: Mesa Redonda Heridas de cuello; coordinador Guaymirán Ríos Bruno - Ríos Bruno, Guaymirán (Cirugía del Uruguay, 1974)
Congressional authorities have believed appropriate to consider, in it, a topic of of practical importance such as "Wounds De cueUo ", and have been kind enough to relapse to the Emergency Department through one of its representatives, the honor to lead this round table